THE ESSENCE OF THE PHENOMENON, PROBLEMS AND RISKS OF THE FORMATION AND DEVELOPMENT OF THE DIGITAL ECONOMY - Mirzarakhimova A. B. (Modern American Journals, 2025)
Today, new digital technologies and innovative business models penetrate into all spheres of the country's economic life. Society influences the essence of the economy, forming qualitative structural changes in it. The digital economy as a subsystem of the traditional economy, characterized by the active use of digital technologies and, as a result, the turnover of specific electronic goods is formed. The level of development of the digital economy closely correlates with the competitiveness of the country, which requires special attention from the state and business to its development. The article presents an overview of the development of digital technologies, the risks and threats of the development of the digital economy are identified and directions for overcoming them are proposed. It has been established that today the electronic economy is already going beyond purely economic processes. Digitalization is being introduced into social processes, the successful activity of people increasingly depends on it, in addition, large-scale introduction of digital technologies into the work of government organizations and structures is taking place. Cooperation between the state and business in the further development of the digital economy is necessary.
Keywords: Digital economy, threats and risks to sustainable development, economic growth, state regulation of the economy, scientific and technological progress.